Organize - Beyes, Timon; Conrad, Lisa; Martin, Reinhold; Lovink, Geert; Rossiter, Ned; Beyes, Timon; Conrad, Lisa; Martin, Reinhold; Lovink, Geert; Rossiter, Ned (meson press, 2019)
Digital media technologies re-pose the question of organization$1 (Band thus of power and domination, control and surveillance, disruption and emancipation. This book interrogates organization as effect and condition of media. How can we understand the recursive relationship between media and organization? How can we think, explore, critique$1 (Band perhaps alter$1 (Bthe organizational bodies and scripts that shape contemporary life?s
English
Keywords: Film, TV & radio; organization; digital media